Pleuropulmonary Ultrasound in Pediatrics: Proposal of a Reporting Model From the Academy of Thoracic Ultrasound. (29th December 2021) - Amendolea, Antonella; Gori, Laura; Adamoli, Paolo; Limoli, Giuseppe; Supino, Maria Chiara; Coco, Alfina Domenica; Trobia, Gian Luca; Tursi, Francesco; Soldati, Gino; Buonsenso, Danilo; ,
Abstract : With the emergence of the Covid‐19 pandemic, pleuropulmonary ultrasound has become a very common tool in clinical practice, even in the pediatric field. Therefore, the clinicians' need to speak a common ultrasound language becomes increasingly necessary. The Italian scientific society AdET (Academy of Thoracic Ultrasound) has been carrying out the study and dissemination of pulmonary ultrasound in medical practice in Italy for years. With this article, the pediatric AdET group wants to propose a report model of pediatric pulmonary ultrasound as a useful tool in daily clinical practice to interpret the images and reach a diagnostic conclusion, aiming to share a standardized approach that may also support the sharing of research findings.